Relationships between expectation towards technology and social gratification with continuance intention to watch movies on YouTube: mediating roles of gratification / Mohd Syuhaidi Abu Bakar and Jusang Bolong. - Abu Bakar, Mohd Syuhaidi; Bolong, Jusang (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2018)
This study hypothesized that gratification mediates relationships between expectations towards social and technology gratification provided by YouTube for movie watching experience; with continuance intention of using YouTube to watch movies. All variables and items were extracted from reviews of literatures and were checked for convergent and discriminant validity using Confirmatory Factor Analysis (CFA). Structural Equation Modelling (SEM) under AMOS software was later used. Results of the SEM indicated that the model fits the data. Based on the Three-Variable Non-recursive Causal Model by Baron and Kenny, it was found that gratification acts as a mediator for both expectations, which also led to their continuance intent to watch movies on YouTube.